Assessing the conservation status of wild banana genetic resources by means of population genetics and distribution modelling - Mertens, A. (Katholieke Universiteit Leuven, 2023)
Crop wild relatives (CWR) are wild plant species that are closely related or ancestral to cultivated plants. Because they often have high allelic diversity compared to their associated crop, they are an important source for the improvement of multiple agronomic traits such as yield or the resistance against biotic or abiotic stresses. Loss of genetic diversity due to increasing anthropogenic pressure now threatens their long term survival. There is a growing recognition of the importance of CWR and more ex- and in-situ conservation efforts to protect this diversity are implemented. In-situ conservation involves protecting the species’ natural habitat and has the advantage that species are still being exposed to natural selective forces that might stimulate new genetic variation. Ex-situ conservation is the long term conservation of species accessions in specialised institutes such as botanical gardens, seed banks, in-vitro gene banks or cryogenic tanks, allowing also the distribution of germplasm for scientists, farmers and plant breeders. Despite increasing CWR conservation efforts, CWR are still often represented by a limited number of accessions that do not cover their entire geographic range and only cover a fraction of their genetic diversity. More efficient collecting, conservation, and use of CWR requires knowledge on what is currently missing in collections. However, passport data of many accessions are incomplete, complicating the identification of conservation gaps. Bananas and plantains (Musaceae) are the leading fruit crop and one of the most important food crops in the world next to rice, maize, and wheat. While over 1,200 varieties are grown worldwide, these cultivars are derived from a small gene pool, making them highly susceptible to biotic and abiotic diseases. Despite the high number of cultivated material in ex-situ collections, wild banana species are largely underrepresented in these gene banks, and often only with one or few accessions. Decreasing suitable habitat and genetic diversity through anthropogenic pressure and the need to find new germplasm for breeding purposes stresses the need for additional conservation efforts. To make efficient future collecting and conservation feasible, we have to know the current conservation status of banana CWR, both in- and ex-situ, the extent of the genetic diversity that is currently already available in gene banks, and where novel diversity can be found and collected. This is mainly important for wild Musa acuminata and M. balbisiana that make up the genetic constitution of almost all the existing cultivars today. In this thesis, we provide a basis for a more efficient, targeted collection and conservation of banana CWR, with a focus on M. balbisiana. This was accomplished at three different levels. First, we assessed environmental suitability, the conservation status, and extinction risk for most Musa CWR across their distribution range using a species distribution modelling approach and red list criteria of the International Union for Conservation of Nature (IUCN). We present that rainforests of northern Indo-Burma have the highest suitability for most wild banana species and show that almost all banana CWR are currently insufficiently conserved both in- and ex-situ, but especially ex-situ. Second, we sampled leaf and seed material of M. balbisiana in Vietnam and genotyped them using 18 SSR markers. We screened for the first time the genetic variation within and between M. balbisiana populations of Vietnam and compared this with genetic variation found in populations from China. We additionally assessed population genetic structure of these populations across the geographic gradient. Relatively high variation was found in populations of China, Central Vietnam and populations of northern Vietnam west of the Hoang Lien Son mountain range. Highest level of genetic variation was found in populations of Central Vietnam, which also exhibited a high number of unique alleles. Low genetic variation was found in populations near the Red River and in South Vietnam. We propose that populations from South Vietnam are not native and that conservation efforts should focus on populations from Central Vietnam and west of the mountain range in northern Vietnam. Third, we assessed to what extent the genetic diversity of M. balbisiana in Vietnam was already conserved ex-situ at the International Musa Germplasm Transit Centre (ITC) and identified areas in Southeast Asia that require additional collecting. For this, we requested and screened all available ITC germplasm accessions of wild Musa balbisiana and compared them to more recently collected samples from China, Vietnam, and Papua New Guinea. Analyses of population structure revealed that only one ITC accession grouped with native M. balbisiana populations and that all other ITC accessions were assigned to a separate cluster. Many ITC accessions from different countries of origin were genetically similar or identical to samples from home gardens in Vietnam, questioning their wild origin. Most ITC accessions were genetically distinct from samples from wild populations, highlighting that they are a valuable source of unique genetic variation of M. balbisiana, but that additional germplasm should be collected from the native distribution range, especially from Northeast India, Myanmar, China, and the Philippines. Insufficient accessions from these countries and the lack of passport data made it hard to interpret genetic information in relation to cultivation and to confirm whether M. balbisiana in the Philippines is native or not.